Rekonfigurasi Saluran Distribusi 20 kV Untuk Mengurangi Rugi-Rugi Daya dan Jatuh Tegangan Pada Penyulang Abang - Arya Suardika, I Putu; Dyana Arjana, I Gede; Maharta Pemayun, Anak Agung Gede (Jurnal SPEKTRUM, 2018)
The feeder of Abang is one of forty-one feeders in State Electrical Company (PT PLN) of east Bali Area. This feeder uses a configuration of radial type that serves consumers in the area of Padangkerta, Bias, Batannyuh, Kikian, Ababi, Datah, Kubu, Nusu, Tianyar and Ban. It has a line transect that is 212,8 kms in leght with a total of distribution subtatations of 167 transformers and its peaks load reaches 5669 kW. This conditions results in drop voltage of 16,255% and and power losses of 10,12%. Feeder reconfiguration is accomplished by two ways: the cutting of the network that is diverted to Subagan feeder and the planning of Kubu feeder. Reconfiguration by using a method of cutting the network shows a voltage correction of Abang feeder with the initial drop voltage of 16,255% to 3.05% and the initial power losses of 10,12% to 3,49%. The improvement of voltage and power losses occurring in this feeder is not followed by Subagan feeder, which experienced an initial rise in the percentage of drops voltage of 6,78% to 27,615% and its initial power losses of 3,89% to 13,28%. While reconfiguration with Kubu's feeder planning is able to repair the drop voltage of Abang feeder to 2.94% and its power losses to 3,41%. Meanwhile, Kubu’s feeder in accordance with the results of running the program ETAP that the value of drop voltage is 2,95% and power losses is 2,73%.